Current concepts in dental adhesives - Sunico, Michelle C. (The Journal of the Philippine Dental Association)
This article is a compilation of the lates advances in dental adhesive technology and aims to give the reader an overview of the current recommendations, practical tips and answer commonly asked questions on the use of present day denta adhesives, A brief sumamry on the different generations of dental adhesives, their usage, the differences in their chemistry and examples of each generation of dental adhesives is also included.